The first experience of application of ICG-fluorescence for detection of segmental plane formation in thoracoscopic segmentectomy - V. G. Pishchik; A. I. Kovalenko; E. I. Zinchenko; A. D. Obornev (Вестник хирургии имени И.И. Грекова, 2017)
OBJECTIVE. The authors evaluated the first European experience of fluorescence thoracoscopy with indocyanine green (ICG) in light spectrum which was approximated to near-infrared (NIR) in thoracoscopic segmentectomy (VATS segmentectomy). MATERIALS AND METHODS. The study covered 21 patients who underwent thoracoscopic segmentectomy during 2016. The ICG (0,15 mg/kg of body weight) was injected intravenously after dominant pulmonary artery ligation during operation. The boundary line between areas was marked by electrocautery at the border of fluorescence. RESULTS. The well-defined fluorescence borders were observed in 18 out of 21 patients (85,7 %). The median duration of intensive ICG staining was 95 sec and that was enough to mark intersegmental plane. The intraoperative verification was unsuccessful in 2 patients due to technical reasons. The first attempt of identification for the patient with severe COPD had unconvincing results and an additional ICG injection was used to achieve the precise fluorescence. There wasn’t revealed any complications associated with ICG injection. CONCLUSIONS. The ICG fluorescence is safe and effective method of segmental plane location. The implementation of this method significantly facilitates in thoracoscopic segmentectomy. The NIR fluorescence imaging systems allow clinicians to work with lower doses of ICG.